Pink hats and ballots : an ecofeminist analysis of women's political activism in the age of Trump, coronavirus, and Black Lives Matter /: an ecofeminist analysis of women's political activism in the age of Trump, coronavirus, and Black Lives Matter. (2021) - Rose, Lydia; Bartoli, Teresa M
No abstract available